THE EFFECT OF SLEEP DURATION ON SCHOOL ACTIVITIES - Akhtar Faatihah Rajani; Naufal Radithya Akbar (PT. Radja Intercontinental Publishing, 2025)
This literature review discusses the effect of sleep duration on students’ school activities, focusing on learning engagement, concentration, and academic performance. Based on an analysis of 20 scientific articles published between 2015 and 2024, a consistent positive correlation was found between adequate sleep and optimal cognitive function. Learners who consistently obtain more than seven hours of sleep per night tend to demonstrate better academic results, participate more actively in learning activities, and show greater emotional stability compared to sleep-deprived students. Research also indicates that poor sleep habits can lead to fatigue, mood disturbances, and decreased motivation to learn. Therefore, this study asserts that sufficient sleep is essential to support students’ performance at school and recommends the promotion of sleep hygiene education in both school and home environments to encourage adolescents to adopt healthy sleep habits.